Haematological, Serum Biochemical and Histopathological Changes in Acute and Sub-Chronic Aqueous Extract of Oyster Mushroom in Male Wistar Rats (Journal of Scientific Research, 2023)
This study aimed at evaluating toxicological implications of aqueous P. ostreatus extract (POE) in male Wistar rats. POE was prepared in 1:10 (pulverized P. ostreatus : distilled water). In  acute toxicity test, single oral dose of 2 mL/kg of POE was administered and observed for 28 days. The sub-chronic toxicity study was conducted by daily oral administration of graded doses (0.25, 0.50 and 0.75 mL/kg b.w) of the extract for 28 days. Clinical signs of toxicity, hematological, serum biochemical parameters and histopathological studies were subsequently evaluated. No treatment-related signs of toxicity or mortality in the animals were recorded in both toxicity tests. Rats administered with lowest dose of POE (25 mL/kg) had highest percentage weight gain. POE had no significant difference (P>0.05) on Red Blood Cell, White Blood Cell (WBC) and differential WBC, and serum biochemistry across all the treated groups when compared to the controls. The result of photomicrographs of stomach, spleen, heart, lung, kidney and liver showed a well outlined arrays of normal tissues in both acute and sub-chronic doses connoting that POE had no toxic effect on them. In view of these, POE may be concluded to be non-toxic within the tested doses and period of investigation.